STRATEGI PENGEMBANGAN EKOWISATA BERBASIS EKONOMI LOKAL STUDI KASUS AEK SIJORNI KEC. SAYUR MATINGGI TAPANULI SELATAN SUMATERA UTARA - Astri Hardina Amelia; Muhammad Arif; Muhammad Ikhsan Harahap (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
The purpose of this research is to examine or find out the strength of the local economy and the strategies that encourage the development of Aek Sijorni's ecotourism potential. This research uses a qualitative approach method. The type of data used in this research is primary and secondary data. Data collection techniques through interviews, documentation. The informant in this research was Arif Firmansyah as Chair of the Tourism Awareness Group (Pokdarwis) of Aek Sijorni Tourism Village. The data analysis techniques used in this research are data reduction, data presentation and drawing qualitative descriptive conclusions. The research results stated that the Aek Sijorni Tourism Village had gone through planning management. The strength of the local economy in the Aek Sijorni Tourism Village, the community carries out economic activities by opening stalls, tourist rides, travel agencies and so on. A strategy that can encourage Aek Sijorni's ecotourism potential is to use a planning approach. The first is planning to develop facilities and infrastructure such as building access to tourist attractions, building new outbound rides, and other supporting facilities. The two human resource institutional plans for this program improve the quality of human resources. The program is held regularly in the form of Pokdarwis training. Third, with tourism marketing planning so that it is known to the wider community.